2018
DOI: 10.1111/ddi.12866
|View full text |Cite
|
Sign up to set email alerts
|

Remaining populations of an upland stream fish persist in refugia defined by habitat features at multiple scales

Abstract: Aim Conserving stream biota could require strategies that preserve habitats conveying resistance to ecological impacts of changing land use and climate. Retrospective analyses of species’ responses to anthropogenic disturbances can inform such strategies. We developed a hierarchical framework to contrast environmental conditions underlying persistence versus extirpation of an imperilled stream fish, Candy Darter (Etheostoma osburni), over decades of changing land use. The decline of E. osburni may broadly repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 79 publications
(125 reference statements)
1
5
0
Order By: Relevance
“…Past studies within the UMNR have emphasized declines of a few resident species (Buckwalter et al, 2018;Dunn & Angermeier, 2019), but none has indicated the mass community-and species-level losses in fish diversity suggested by our analysis. This new insight stems from our innovative analytical approach focused on species abundance rather than species occurrence as the measure of spread and decline.…”
Section: Species-level Abundance Trendsmentioning
confidence: 63%
“…Past studies within the UMNR have emphasized declines of a few resident species (Buckwalter et al, 2018;Dunn & Angermeier, 2019), but none has indicated the mass community-and species-level losses in fish diversity suggested by our analysis. This new insight stems from our innovative analytical approach focused on species abundance rather than species occurrence as the measure of spread and decline.…”
Section: Species-level Abundance Trendsmentioning
confidence: 63%
“…In the Other Threats node, we included the combined deleterious effects of Hybridization (i.e., documented presence of hybrids involving the species) and Nonnative Species (i.e., nonnative fish richness) detected within a management unit (Table 1). These threats were factors imperiling multiple southeastern U.S. species listed recently as Endangered under the ESA (e.g., Barrens Topminnow, Fundulus julisia , Ennen et al, 2021; Candy Darter, Etheostoma osburni , Dunn & Angermeier, 2019). The Other Threats node could be adapted to reflect alternative species‐specific threats or habitat conditions (e.g., stream warming, land‐use change, and water quality; Noss et al, 2021) or to explicitly accommodate threats outlined by policy (e.g., Five Factors under ESA; Shirey et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Our objectives were to quantify the multi‐scale habitat related to the presence and abundance of Neosho Smallmouth Bass nests, to describe factors related to nest aggregations (hereafter “clusters”), and to quantify nest microhabitat conditions. Multi‐scale approaches are increasingly used in warmwater stream‐fisheries research (e.g., Dunn & Angermeier, 2019; Wellemeyer et al., 2019). For example, Dunn and Angermeier (2019) show that imperilled Candy Darter ( Etheostoma osburni ) persistence requires refugia conferred by habitat conditions at local (i.e., temperature, sedimentation) and catchment (i.e., land use) spatial scales.…”
Section: Introductionmentioning
confidence: 99%
“…Multi‐scale approaches are increasingly used in warmwater stream‐fisheries research (e.g., Dunn & Angermeier, 2019; Wellemeyer et al., 2019). For example, Dunn and Angermeier (2019) show that imperilled Candy Darter ( Etheostoma osburni ) persistence requires refugia conferred by habitat conditions at local (i.e., temperature, sedimentation) and catchment (i.e., land use) spatial scales. However, most efforts to understand hierarchical controls on warmwater stream fish abundance focus on adult fish outside of the reproductive period (but see Peoples et al., 2014).…”
Section: Introductionmentioning
confidence: 99%